The effect of strain hardening on the behavior of the AISI 304 stainless steels alloys under dry friction - Reinoza, Rigoberto; Guillén, Alexo (Rev. Téc. Fac. Ing. Univ. Zulia, 2010)
The effect of strain hardening on the behavior of austenitic stainless steel AISI 304 under dry friction wear, has been studied. The martensitic microstructure behavior of stainless steel AISI 420 has been used as a comparative pattern with austenitic microstructure. Both microstructures were subjected to three different loads during five different contact times and to a constant turn speed. The wear in the sample type disks of each one of the microstructures was determined by means of the weight lost. Tests result analysis based on weight lost and the hardness changes on austenitic microstructure show that strain hardening effect improves the wear strength of this microstructure.